A bio-based degradable composite oxygen barrier film and its preparation method and application
By grafting the amphiphilic molecular chains on the surface of cellulose nanocrystals, the problem of insufficient barrier performance of cellulose nanocrystals/PLA composites is solved, and the effect of significantly improving barrier performance is achieved.
Patent Information
- Application Number
- CN202310040177.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-13
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-01-13
AI Technical Summary
The barrier properties of existing cellulose nanocrystals/PLA composites are insufficient, mainly due to the poor dispersion of cellulose nanocrystals in PLA and the low interfacial bonding strength, which makes it impossible to meet the high barrier requirements.
The dispersion and interface binding strength in PLA are enhanced by grafting the amphiphilic molecular chains on the surface of cellulose nanocrystals. The specific method includes amidation reaction to prepare aminated cellulose nanocrystals, and grafting the hydrophobic carbon chain at the end of the polar molecular chain of the end of the amine group through a reduction amination reaction to form amphiphilic molecular link branch modified cellulose nanocrystals.
The dispersion and interface bonding strength of cellulose nanocrystals in PLA are significantly improved, and the barrier properties of PLA are significantly enhanced under low filling amounts, achieving the effect of high oxygen-resistance film.
Smart Images

Figure BDA0004050598860000141 
Figure BDA0004050598860000161 
Figure HDA0004050598870000011
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer nanocomposite films, and specifically relates to a bio-based degradable high oxygen barrier film and a preparation method and application thereof. Background Art
[0002] Petroleum-based polymers have been widely used in packaging and protection fields such as electronics, food, medicine, and aviation due to their advantages such as easy processing, low cost, and good flexibility. However, while the large-scale use of barrier materials has brought convenience to mankind, it has also caused serious environmental pollution and aggravated human society's dependence on increasingly depleted petrochemical resources. The development of green and renewable barrier materials is the main way to solve the current environmental pollution and resource shortages. Polylactic acid (PLA), as a renewable material, has become one of the most promising degradable polymers in the market due to its biodegradability, abundant sources, and stable performance. However, its poor gas barrier properties limit its promotion and application in the packaging field. Therefore, improving the gas barrier properties of PLA is the key to expanding its development and application.
[0003] Cellulose nanocrystals (CNCs) are a type of nanomaterial derived from plant fibers. They are biodegradable, renewable, and have excellent barrier and mechanical properties, making them a new generation of green nano-reinforced fillers. However, due to the hydrophilicity of their surface, CNCs have problems such as difficulty in dispersion, easy agglomeration, and weak interface bonding in hydrophobic PLA, which cannot fully exert their excellent barrier performance enhancement effect, resulting in the barrier properties of CNCs / PLA composites not being able to meet the high barrier requirements of actual projects. At present, the methods for improving the barrier properties of CNCs / PLA composites mainly focus on the hydrophobic modification of CNCs, and improving the dispersibility of CNCs in PLA by hydrophobic modification. However, the improvement of the barrier properties of the materials is very limited. The limitation of the existing technology is that the influence of CNCs-PLA interface bonding is not considered. For CNCs / PLA materials, in addition to dispersibility, interface bonding strength is another key factor affecting the overall material performance. At present, there are no reports on the research of cellulose nanocrystal / PLA oxygen barrier films modified by amphiphilic molecular chains. Summary of the invention
[0004] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a bio-based degradable high oxygen barrier film.
[0005] The present invention simultaneously improves the dispersibility and interface bonding strength of cellulose nanocrystals in PLA by grafting amphiphilic molecular chains on the surface of cellulose nanocrystals; the amidation reaction between the carboxyl groups on the surface of carboxylated cellulose nanocrystals and the terminal amine polar molecular chains is used to prepare aminated cellulose nanocrystals, and then the hydrophobic carbon chain is grafted on the end of the terminal amine polar molecular chain by the reductive amination reaction between the amine groups on the surface of the aminated cellulose nanocrystals and fatty aldehydes, so as to obtain amphiphilic molecular chain grafted modified cellulose nanocrystals. On the one hand, the amine groups in the polar molecular chains grafted on the surface of the cellulose nanocrystals can form hydrogen bonds with the carbonyl oxygen in PLA, thereby enhancing the interface bonding; on the other hand, the hydrophobic segments can enhance the compatibility of CNCs and PLA through van der Waals forces and physical entanglement. The synergistic effect of these two aspects can maximize the dispersibility of cellulose nanocrystals in PLA and the interface bonding strength of CNCs-PLA, thereby significantly enhancing the barrier properties of PLA at a low filling amount (≤5wt%).
[0006] The amphiphilic molecular link grafted modified cellulose nanocrystal / PLA high oxygen barrier film of the present invention can effectively solve the problem of poor oxygen barrier property of current degradable oxygen barrier films.
[0007] Another object of the present invention is to provide a method for preparing the above-mentioned bio-based degradable high oxygen barrier film.
[0008] Another object of the present invention is to provide an application of the above-mentioned bio-based degradable high oxygen barrier film.
[0009] The purpose of the present invention is achieved through the following technical solutions:
[0010] A bio-based degradable oxygen barrier film is composed of polylactic acid (PLA) and amphiphilic molecular chain-grafted modified cellulose nanocrystals, wherein the mass percentage of the amphiphilic molecular chain-grafted modified cellulose nanocrystals in the oxygen barrier film is 1-5%, the cellulose nanocrystals are carboxylated cellulose nanocrystals, and the amphiphilic molecular chain is -(NH-CH2-CH2) x -NH-(CH2) y-1 -CH3, wherein x is 2, 3, 4 or 5, and y is 1, 2, 3 or 4.
[0011] Preferably, the amphiphilic molecular chain grafted modified cellulose nanocrystals are prepared by an amidation reaction between the carboxyl groups on the surface of the carboxylated cellulose nanocrystals and the polar molecular chains of the terminal amine groups to form aminated cellulose nanocrystals, and then by a reductive amination reaction between the amine groups on the surface of the aminated cellulose nanocrystals and fatty aldehydes.
[0012] More preferably, the ratio of the terminal amine polar molecular chain to the carboxylated cellulose nanocrystal is 2-20 mmol:1 g, and most preferably 7.5-10 mmol:1 g; the ratio of the fatty aldehyde to the aminated cellulose nanocrystal is 2-20 mmol:1 g, and most preferably 7.5-10 mmol:1 g.
[0013] More preferably, the terminal amine polar molecular chain is at least one of diethylenetriamine, triethylenetetramine, tetraethylenepentamine and pentaethylenehexamine; and the fatty aldehyde is at least one of formaldehyde, acetaldehyde, propionaldehyde and butyraldehyde.
[0014] The above-mentioned method for preparing a bio-based degradable oxygen barrier film comprises the following steps:
[0015] (1) dispersing carboxylated cellulose nanocrystals (TOCNCs) in water, adding a carboxyl activator and an amine-terminated polar molecular chain, adjusting the pH, reacting at room temperature for 12 to 48 hours, and obtaining an aminated cellulose nanocrystal aqueous dispersion by membrane dialysis;
[0016] (2) adding fatty aldehyde and reducing agent to the aqueous dispersion of aminated cellulose nanocrystals, reacting at room temperature for 12 to 48 hours, and then centrifuging, washing, and freeze-drying to obtain amphiphilic molecular chain-grafted modified cellulose nanocrystals (LH@CNCs);
[0017] (3) The amphiphilic molecular chain grafted modified cellulose nanocrystals are subjected to solvent replacement to obtain an amphiphilic molecular chain grafted modified cellulose nanocrystal dispersion, i.e., solution I; PLA is dissolved in a solvent to obtain solution II; solution I and solution II are evenly mixed to obtain a film-forming liquid, which is defoamed and dried to obtain a bio-based degradable high oxygen barrier film.
[0018] Preferably, the concentration of the carboxylated cellulose nanocrystals (TOCNCs) dispersed in water in step (1) is 0.1 to 3.0 mg / ml.
[0019] Preferably, the carboxyl activator in step (1) is N-hydroxysuccinimide (NHS) and 1-ethyl-(3-dimethylaminopropyl) (EDC); the mass ratio of 1-ethyl-(3-dimethylaminopropyl) (EDC), N-hydroxysuccinimide (NHS) and carboxylated cellulose nanocrystals (TOCNCs) is (0.5-2): (0.5-2): 1, preferably 1:1:1.
[0020] Preferably, the ratio of the terminal amine polar molecular chain to carboxylated cellulose nanocrystals (TOCNCs) in step (1) is 2-20 mmol:1 g, most preferably 7.5-10 mmol:1 g; the terminal amine polar molecular chain is at least one of diethylenetriamine, triethylenetetramine, tetraethylenepentamine and pentaethylenehexamine.
[0021] Preferably, the pH in step (1) is 3-6, preferably 4-5.
[0022] Preferably, in step (2), the ratio of the fatty aldehyde to carboxylated cellulose nanocrystals (TOCNCs) is 2-20 mmol:1 g, more preferably 7.5-10 mmol:1 g; the fatty aldehyde is at least one of formaldehyde, acetaldehyde, propionaldehyde and butyraldehyde.
[0023] Preferably, the reducing agent in step (2) is sodium triacetoxyborohydride (STAB); the ratio of the reducing agent to carboxylated cellulose nanocrystals (TOCNCs) is 2-20 mmol:1 g, more preferably 7.5-10 mmol:1 g.
[0024] Preferably, the concentration of the aqueous dispersion of aminated cellulose nanocrystals in steps (1) and (2) is 0.1 to 3 mg / mL, more preferably 0.5 to 2 mg / mL.
[0025] Preferably, the solvent replacement in step (3) refers to: dispersing the amphiphilic molecular chain grafted modified cellulose nanocrystals in dimethylformamide (DMF), and replacing them with acetone and / or ethanol, chloroform (CHCl3) and / or dichloromethane in sequence to obtain a chloroform dispersion of amphiphilic molecular chain grafted modified cellulose nanocrystals; wherein acetone and / or ethanol can be replaced with a solvent that is miscible with DMF and chloroform / and or dichloromethane at the same time and has a dispersibility for CNCs between DMF and chloroform / and or dichloromethane; the solvent of solution II is at least one of chloroform and dichloromethane.
[0026] More preferably, the concentration of the amphiphilic molecular link grafted modified cellulose nanocrystals dispersed in dimethylformamide (DMF) is 0.1-3 mg / mL, more preferably 0.5-2 mg / mL; the concentration in chloroform (CHCl3) and / or dichloromethane is 0.1-5 mg / mL, more preferably 1 mg / mL.
[0027] Preferably, the concentration of solution I in step (3) is 0.1-5 mg / mL, more preferably 1 mg / mL; the concentration of solution II is 0.01-0.5 g / mL, preferably 0.1 g / mL; the volume ratio of solution I to solution II is (1-5):1, more preferably (2.5-3.5):1.
[0028] Preferably, the debubbling treatment in step (3) refers to removing bubbles by ultrasonic treatment.
[0029] Preferably, the drying in step (3) is carried out at room temperature for 48 to 72 hours, wherein the room temperature is 10 to 30° C., and more preferably at 20 to 30° C. for 50 to 60 hours.
[0030] Preferably, the film-forming liquid in step (3) is poured into a mold and dried.
[0031] Preferably, the normal temperature in steps (1) to (2) refers to 10 to 40°C.
[0032] The above-mentioned bio-based degradable oxygen barrier film is used in the field of food packaging.
[0033] The bio-based degradable oxygen barrier film is used in the field of food packaging and can be used as a packaging bag or a cling film in the packaging and preservation of vegetables, fruits and melons and has a wide range of applications.
[0034] The core principle of the technology of the present invention: The present invention improves the dispersibility and interfacial bonding strength of cellulose nanocrystals in PLA by grafting amphiphilic molecular chains in modified cellulose nanocrystals with amphiphilic molecular chains. The amine groups on the polar chains on the surfaces of the modified cellulose nanocrystals with amphiphilic molecular chains form hydrogen bonds with the carbonyl oxygen in polylactic acid, thereby enhancing the interfacial bonding strength between the cellulose nanocrystals and polylactic acid. At the same time, the hydrophobic segments on the surfaces of the modified cellulose nanocrystals with amphiphilic molecular chains can not only enhance the compatibility with the hydrophobic polylactic acid, but also act as a "hat" to hinder the interaction between cellulose nanocrystals and significantly reduce the agglomeration of cellulose nanocrystals. Therefore, the grafted amphiphilic molecular chains can ensure the good dispersibility of cellulose nanocrystals while enhancing the interfacial bonding strength. The synergistic effect of the two aspects can maximize the excellent barrier performance enhancement effect of cellulose nanocrystals and achieve high oxygen barrier properties of CNCs / PLA composite films.
[0035] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0036] (1) The high oxygen barrier composite membrane provided by the present invention is degradable and renewable. Compared with traditional petroleum-based polymer membranes, it can effectively alleviate the problem of white pollution and dependence on petroleum resources, and help implement my country's "dual carbon" plan.
[0037] (2) The present invention uses amphiphilic molecular chain grafted cellulose nanocrystals as fillers to prepare PLA composite films, which can maximize the dispersibility of cellulose nanocrystals while achieving strong interfacial bonding. The dispersibility and interfacial bonding together give the PLA composite film excellent oxygen barrier properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 Schematic diagram of the modification principle of cellulose nanocrystals, x=2, 3, 4, 5; y=1, 2, 3, 4.
[0039] Figure 2 This is the infrared spectrum of the modified cellulose nanocrystals in Example 10. DETAILED DESCRIPTION
[0040] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.
[0041] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.
[0042] Example 1
[0043] Weigh 100 mg TOCNCs and place it in 1000 ml deionized water for ultrasonic treatment for 0.5 h; add EDC and NHS (50 mg each) and stir (300 rpm) at room temperature for reaction for 30 min; add 2 mmol diethylenetriamine and adjust the pH to 6 with hydrochloric acid; continue to stir (300 rpm) at room temperature for reaction for 24 h; dialyze in deionized water until neutral to obtain an aminated cellulose nanocrystal dispersion, add 200 mg of 30% formaldehyde aqueous solution and 2 mmol STAB, stir (300 rpm) at room temperature for reaction for 24 h, centrifuge, wash and freeze-dry to obtain cellulose nanocrystals A-EDTA@CNCs modified with amphiphilic molecular chains (CH3-(NHCH2CH2)2-NH-).
[0044] Example 2
[0045] Referring to the modification method of cellulose nanocrystals in Example 1, 1 mmol of triethylenetetramine was used instead of 2 mmol of diethylenetriamine, the amount of 30% formaldehyde aqueous solution was changed from 200 mg to 100 mg, and the amount of STAB was changed from 2 mmol to 1 mmol. The other parameters and reaction conditions remained unchanged to obtain cellulose nanocrystals A-TETA@CNCs modified with amphiphilic molecular chains (CH3-(NHCH2CH2)3-NH-).
[0046] Example 3
[0047] 100 mg TOCNCs was placed in 200 ml deionized water and ultrasonicated for 1 hour. 100 mg of EDC and NHS were added thereto, and the mixture was stirred and reacted at 300 rpm for 30 minutes at room temperature. 0.75 mmol of tetraethylenepentamine was added, and the pH was adjusted to 5.5 with hydrochloric acid. The mixture was stirred and reacted at 300 rpm for 24 hours at room temperature. The mixture was dialyzed in deionized water until neutral, and 75 mg of 30% formaldehyde aqueous solution and 0.75 mmol of STAB were added thereto. The mixture was stirred and reacted at 300 rpm for 24 hours at room temperature. After centrifugation, washing and freeze-drying, cellulose nanocrystals A-TEPA@CNCs modified with amphiphilic molecular chains (CH3-(NHCH2CH2)4-NH-) were obtained.
[0048] Example 4
[0049] Referring to the modification method of cellulose nanocrystals in Example 3, 0.5 mmol pentaethylenehexamine was used instead of 0.75 mmol tetraethylenepentamine, the amount of 30% formaldehyde aqueous solution was changed from 75 mg to 50 mg, and the amount of STAB was changed from 0.75 mmol to 0.5 mmol. The other parameters and reaction conditions remained unchanged to obtain cellulose nanocrystals A-PEHA@CNCs modified with amphiphilic molecular chains (CH3-(NHCH2CH2)5-NH-).
[0050] Example 5
[0051] 100 mg TOCNCs was placed in 100 ml deionized water and ultrasonicated for 1 hour. 150 mg of EDC and NHS were added thereto, and the mixture was stirred and reacted at 300 rpm for 30 minutes at room temperature. 2 mmol of diethylenetriamine modifier was added, and the pH was adjusted to 5 with hydrochloric acid. The mixture was stirred and reacted at 300 rpm for 24 hours at room temperature. After the reaction, the mixture was dialyzed in deionized water until neutral. 200 mg of 40% acetaldehyde aqueous solution and 2 mmol STAB were added thereto, and the mixture was stirred and reacted at 300 rpm for 36 hours at room temperature. After centrifugation, washing and freeze-drying, (CH3CH2-(NHCH2CH2)2-NH-)amine-modified cellulose nanocrystals B-EDTA@CNCs were obtained.
[0052] Example 6
[0053] Referring to the modification method of cellulose nanocrystals in Example 5, 1.5 mmol of triethylenetetramine was used to replace 2 mmol of diethylenetriamine, the amount of 40% acetaldehyde aqueous solution was changed from 240 mg to 180 mg, and the amount of STAB was changed from 2 mmol to 1.5 mmol. The other parameters and reaction conditions remained unchanged to obtain (CH3CH2-(NHCH2CH2)3-NH-) modified cellulose nanocrystals B-TETA@CNCs.
[0054] Example 7
[0055] 100 mg TOCNCs was placed in 100 ml deionized water and ultrasonicated for 1 hour. 200 mg of EDC and NHS were added thereto, and the mixture was stirred and reacted at 300 rpm for 30 minutes at room temperature. 1 mmol of tetraethylenepentamine was added, and the pH was adjusted to 5 with hydrochloric acid. The mixture was stirred and reacted at 300 rpm for 24 hours at room temperature. The mixture was dialyzed to neutrality in deionized water. 120 mg of 40% acetaldehyde aqueous solution and 1 mmol of STAB were added thereto. The mixture was stirred and reacted at 300 rpm for 12 hours at room temperature. After centrifugation, washing and freeze-drying, (CH3CH2-(NHCH2CH2)4-NH-) modified cellulose nanocrystals B-TEPA@CNCs were obtained.
[0056] Example 8
[0057] 150 mg of TOCNCs was placed in 100 ml of deionized water and ultrasonicated for 1 hour. 300 mg of EDC and NHS were added thereto, and the mixture was stirred and reacted at 300 rpm for 30 minutes at room temperature. 1.125 mmol of pentaethylenehexamine was added, and the pH was adjusted to 4.5 with hydrochloric acid. The mixture was stirred and reacted at 300 rpm for 24 hours at room temperature. The mixture was dialyzed to neutrality in deionized water. 150 mg of 40% acetaldehyde aqueous solution and 1.125 mmol of STAB were added to the above dispersion. The mixture was stirred and reacted at 300 rpm for 24 hours at room temperature. After centrifugation, washing and freeze-drying, (CH3CH2-(NHCH2CH2)5-NH-) modified cellulose nanocrystals B-PEHA@CNCs were obtained.
[0058] Example 9
[0059] 150 mg TOCNCs were placed in 100 ml deionized water and ultrasonicated for 1 hour. 150 mg of EDC and NHS were added thereto, and the mixture was stirred and reacted at 300 rpm for 30 minutes at room temperature. 0.75 mmol of diethylenetriamine was added, and the pH was adjusted to 4.5 with hydrochloric acid. The mixture was stirred and reacted at 300 rpm for 24 hours at room temperature. The mixture was dialyzed to neutrality in deionized water. 0.75 mmol of propionaldehyde and 0.75 mmol of STAB were added to the above dispersion, and the mixture was stirred and reacted at 300 rpm for 24 hours at room temperature. After centrifugation, washing and freeze-drying, (CH3CH2CH2-(NHCH2CH2)2-NH-) modified cellulose nanocrystals C-EDTA@CNCs were obtained.
[0060] Example 10
[0061] Referring to the modification method of cellulose nanocrystals in Example 9, 0.3 mmol of triethylenetetramine was used to replace 0.75 mmol of diethylenetriamine, the amount of propionaldehyde was changed from 0.75 mmol to 0.3 mmol, and the amount of STAB was changed from 0.75 mmol to 0.3 mmol. The other parameters and reaction conditions remained unchanged to obtain (CH3CH2CH2-(NHCH2CH2)3-NH-) modified cellulose nanocrystals C-TETA@CNCs.
[0062] Figure 2 As shown in the infrared spectrum, compared with the original cellulose nanocrystals, the aminated cellulose nanocrystals have a -1 The stretching vibration peak of C=O in the amide bond appears at 1540 cm -1 The NH bending vibration peak of the amide bond appeared at 1257 cm -1 The deformation vibration peak at 1257 cm-1 at the cellulose nanocrystal surface was attributed to -NH2, indicating that the amine chain was successfully grafted onto the surface of the cellulose nanocrystal. -1 The disappearance of the -NH2 vibration peak at indicates that the hydrophobic structure was successfully grafted onto the terminal amino groups of the amino-modified cellulose nanocrystals.
[0063] Embodiment 11
[0064] 200 mg TOCNCs were placed in 100 ml deionized water and ultrasonicated for 1 hour. 200 mg of EDC and NHS were added thereto, and the mixture was stirred and reacted at 300 rpm for 30 minutes at room temperature. 4 mmol of tetraethylenepentamine was added, and the pH was adjusted to 4 with hydrochloric acid. The mixture was stirred and reacted at 300 rpm for 12 hours at room temperature. The mixture was dialyzed to neutrality in deionized water. 4 mmol of propionaldehyde and 4 mmol of STAB were added to the above dispersion, and the mixture was stirred and reacted at 300 rpm for 24 hours at room temperature. After centrifugation, washing and freeze-drying, (CH3CH2CH2-(NHCH2CH2)4-NH-) modified cellulose nanocrystals C-TEPA@CNCs were obtained.
[0065] Example 12
[0066] Referring to the modification method of cellulose nanocrystals in Example 11, 3 mmol pentaethylenehexamine was used to replace 4 mmol tetraethylenepentamine, the amount of propionaldehyde was changed from 4 mmol to 3 mmol, and the amount of STAB was changed from 4 mmol to 3 mmol. The other parameters and reaction conditions remained unchanged to obtain (CH3CH2CH2-(NHCH2CH2)5-NH-) modified cellulose nanocrystals C-PEHA@CNCs.
[0067] Embodiment 13
[0068] 250 mg TOCNCs were placed in 100 ml deionized water and ultrasonicated for 1 h. 250 mg of EDC and NHS were added thereto, and the mixture was stirred and reacted at 300 rpm for 30 min at room temperature. 2.5 mmol of diethylenetriamine was added, and the pH was adjusted to 3.5 with hydrochloric acid. The mixture was stirred and reacted at 300 rpm for 24 h at room temperature. The mixture was dialyzed to neutrality in deionized water. 2.5 mmol of butyraldehyde and 2.5 mmol of STAB were added to the above dispersion, and the mixture was stirred and reacted at 300 rpm for 24 h at room temperature. After centrifugation, washing and freeze-drying, (CH3CH2CH2CH2-(NHCH2CH2)2-NH-) modified cellulose nanocrystals D-EDTA@CNCs were obtained.
[0069] Embodiment 14
[0070] Referring to the modification method of cellulose nanocrystals in Example 13, 1.875 mmol of triethylenetetramine was used to replace 2.5 mmol of diethylenetriamine, the amount of butyraldehyde was changed from 2.5 mmol to 1.875 mmol, and the amount of STAB was changed from 2.5 mmol to 1.875 mmol. The other parameters and reaction conditions remained unchanged to obtain (CH3CH2CH2CH2-(NHCH2CH2)3-NH-) modified cellulose nanocrystals D-TETA@CNCs.
[0071] Embodiment 15
[0072] 300 mg TOCNCs were placed in 100 ml deionized water and ultrasonicated for 1 hour. 300 mg of EDC and NHS were added respectively, and the mixture was stirred and reacted at 300 rpm for 30 minutes at room temperature. 1.5 mmol of tetraethylenepentamine was added, and the pH was adjusted to 3 with hydrochloric acid. The mixture was stirred and reacted at 300 rpm for 24 hours at room temperature. The mixture was dialyzed to neutrality in deionized water. 1.5 mmol of butyraldehyde and 1.5 mmol of STAB were added to the above dispersion, and the mixture was stirred and reacted at 300 rpm for 24 hours at room temperature. After centrifugation, washing and freeze-drying, (CH3CH2CH2CH2-(NHCH2CH2)4-NH-) modified cellulose nanocrystals D-TEPA@CNCs were obtained.
[0073] Example 16
[0074] Referring to the modification method of cellulose nanocrystals in Example 15, 0.6 mmol pentaethylenehexamine was used to replace 1.5 mmol tetraethylenepentamine, the amount of butyraldehyde was changed from 1.5 mmol to 0.6 mmol, and the amount of STAB was changed from 1.5 mmol to 0.6 mmol. The other parameters and reaction conditions remained unchanged to obtain (CH3CH2CH2CH2-(NHCH2CH2)5-NH-) modified cellulose nanocrystals D-PEHA@CNCs.
[0075] Embodiment 17
[0076] 60 mg of A-EDTA@CNCs prepared in Example 1 was ultrasonically dispersed in 60 mL of DMF, dispersed in acetone after centrifugation, and dispersed in 60 mL of CHCl3 after centrifugation to obtain solution I. 1.94 g of PLA was dissolved in 20 mL of CHCl3 to obtain solution II. Solution I and solution II were ultrasonically blended to obtain a membrane-forming solution.
[0077] The obtained film-forming solution was subjected to ultrasonic treatment to remove bubbles, poured into a mold, and dried at room temperature for 48 hours to obtain an A-EDTA@CNCs / PLA composite film, wherein the mass fraction of A-EDTA@CNCs was 3wt%.
[0078] Embodiment 18
[0079] Referring to the film preparation process in Example 17, the A-TETA@CNCs prepared in Example 2 was used to replace the A-EDTA@CNCs, and the other process parameters remained unchanged to prepare the A-TETA@CNCs / PLA composite film, wherein the mass fraction of A-TETA@CNCs was 3wt%.
[0080] Embodiment 19
[0081] Referring to the membrane preparation process in Example 17, the A-TEPA@CNCs prepared in Example 3 was used to replace the A-EDTA@CNCs, and the other process parameters remained unchanged to prepare the A-TEPA@CNCs / PLA composite membrane, wherein the mass fraction of A-TEPA@CNCs was 3wt%.
[0082] Embodiment 20
[0083] Referring to the film preparation process in Example 17, the A-PEHA@CNCs prepared in Example 4 was used to replace the A-EDTA@CNCs, and the other process parameters remained unchanged to prepare the A-PEHA@CNCs / PLA composite film, wherein the mass fraction of A-PEHA@CNCs was 3wt%.
[0084] Embodiment 21
[0085] Referring to the film preparation process in Example 17, B-EDTA@CNCs prepared in Example 5 was used to replace A-EDTA@CNCs, and other process parameters remained unchanged to prepare B-EDTA@CNCs / PLA composite film, wherein the mass fraction of B-EDTA@CNCs was 3wt%.
[0086] Embodiment 22
[0087] Referring to the film preparation process in Example 17, the B-TETA@CNCs prepared in Example 6 was used to replace the A-EDTA@CNCs, the drying time at room temperature was replaced by 60 hours by 48 hours, and the other process parameters remained unchanged to prepare a B-TETA@CNCs / PLA composite film, wherein the mass fraction of B-TETA / CNCs was 3wt%.
[0088] Embodiment 23
[0089] Referring to the film preparation process in Example 17, the B-TEPA@CNCs prepared in Example 7 was used to replace the A-EDTA@CNCs, the drying time at room temperature was replaced by 60 hours to 48 hours, and the other process parameters remained unchanged to prepare a B-TEPA@CNCs / PLA composite film, wherein the mass fraction of B-TEPA@CNCs was 3wt%.
[0090] Embodiment 24
[0091] Referring to the film preparation process in Example 17, B-PEHA@CNCs prepared in Example 8 was used to replace A-EDTA@CNCs, and the drying time at room temperature was replaced by 60 hours to 48 hours. The other process parameters remained unchanged to prepare a B-PEHA@CNCs / PLA composite film, wherein the mass fraction of B-PEHA@CNCs was 3wt%.
[0092] Embodiment 25
[0093] Referring to the film preparation process in Example 17, C-EDTA@CNCs prepared in Example 9 was used to replace A-EDTA@CNCs, and the drying time at room temperature was replaced by 60 hours to 48 hours. The other process parameters remained unchanged to prepare a C-EDTA@CNCs / PLA composite film, wherein the mass fraction of C-EDTA@CNCs was 3wt%.
[0094] Embodiment 26
[0095] Referring to the film preparation process in Example 17, C-TETA@CNCs prepared in Example 10 was used to replace A-EDTA@CNCs, and other process parameters remained unchanged to prepare C-TETA@CNCs / PLA composite film, wherein the mass fraction of C-TETA@CNCs was 3wt%.
[0096] Embodiment 27
[0097] Referring to the film preparation process in Example 17, C-TEPA@CNCs prepared in Example 11 was used to replace A-EDTA@CNCs, and other process parameters remained unchanged to prepare C-TEPA@CNCs / PLA composite membrane, wherein the mass fraction of C-TEPA@CNCs was 3wt%.
[0098] Embodiment 28
[0099] Referring to the film preparation process in Example 17, C-PEHA@CNCs prepared in Example 12 was used to replace A-EDTA@CNCs, and the drying time at room temperature was replaced by 72 hours to 48 hours. The other process parameters remained unchanged to prepare a C-PEHA@CNCs / PLA composite film, wherein the mass fraction of C-PEHA@CNCs was 3wt%.
[0100] Embodiment 29
[0101] Referring to the film preparation process in Example 17, D-EDTA@CNCs prepared in Example 13 was used to replace A-EDTA@CNCs, and the drying time at room temperature was replaced by 72 hours to 48 hours. The other process parameters remained unchanged to prepare a D-EDTA@CNCs / PLA composite film, wherein the mass fraction of D-EDTA@CNCs was 3wt%.
[0102] Embodiment 30
[0103] Referring to the film preparation process in Example 17, D-TETA@CNCs prepared in Example 14 was used to replace A-EDTA@CNCs, and the drying time at room temperature was replaced by 72 hours to 48 hours. The other process parameters remained unchanged to prepare a D-TETA@CNCs / PLA composite film, wherein the mass fraction of D-TETA@CNCs was 3wt%.
[0104] Embodiment 31
[0105] Referring to the film preparation process in Example 17, D-TEPA@CNCs prepared in Example 15 was used to replace A-EDTA@CNCs, and the drying time at room temperature was replaced by 72 hours to 48 hours. The other process parameters remained unchanged to prepare a D-TEPA@CNCs / PLA composite film, wherein the mass fraction of D-TEPA@CNCs was 3wt%.
[0106] Embodiment 32
[0107] Referring to the film preparation process in Example 17, D-PEHA@CNCs prepared in Example 16 was used to replace A-EDTA@CNCs, and the drying time at room temperature was replaced by 72 hours to 48 hours. The other process parameters remained unchanged to prepare a D-PEHA@CNCs / PLA composite film, wherein the mass fraction of D-PEHA@CNCs was 3wt%.
[0108] Embodiment 33
[0109] 20 mg of C-TETA@CNCs prepared in Example 10 was ultrasonically dispersed in 20 mL of DMF, dispersed in acetone after centrifugation, and dispersed in 20 mL of CHCl3 after centrifugation to obtain solution I. 1.98 g of PLA was dissolved in 20 mL of CHCl3 to obtain solution II. Solution I and solution II were ultrasonically blended to obtain a membrane-forming solution.
[0110] The obtained film-forming solution was subjected to ultrasonic treatment to remove bubbles, poured into a mold, and dried at room temperature for 54 hours to obtain a C-TETA@CNCs / PLA composite film, wherein the mass fraction of C-TETA@CNCs was 1wt%.
[0111] Embodiment 34
[0112] 40 mg of C-TETA@CNCs prepared in Example 10 was ultrasonically dispersed in 40 mL of DMF, dispersed in acetone after centrifugation, and dispersed in 40 mL of CHCl3 after centrifugation to obtain solution I. 1.96 g of PLA was dissolved in 20 mL of CHCl3 to obtain solution II. Solution I and solution II were ultrasonically blended to obtain a membrane-forming solution.
[0113] The obtained film-forming solution was subjected to ultrasonic treatment to remove bubbles, poured into a mold, and dried at room temperature for 60 hours to obtain a C-TETA@CNCs / PLA composite film, wherein the mass fraction of C-TETA@CNCs was 2wt%.
[0114] Embodiment 35
[0115] 80 mg of C-TETA@CNCs prepared in Example 10 was ultrasonically dispersed in 80 mL of DMF, dispersed in acetone after centrifugation, and dispersed in 80 mL of CHCl3 after centrifugation to obtain solution I. 1.92 g of PLA was dissolved in 20 mL of CHCl3 to obtain solution II. Solution I and solution II were ultrasonically blended to obtain a membrane-forming solution.
[0116] The obtained film-forming solution was subjected to ultrasonic treatment to remove bubbles, poured into a mold, and dried at room temperature for 66 hours to obtain a C-TETA@CNCs / PLA composite film, wherein the mass fraction of C-TETA@CNCs was 4wt%.
[0117] Embodiment 36
[0118] 100 mg of C-TETA@CNCs prepared in Example 10 was ultrasonically dispersed in 100 mL of DMF, dispersed in acetone by centrifugation, dispersed in 100 mL of CHCl3 by centrifugation, and dispersed in 100 mL of CHCl3 to obtain solution I. 1.90 g of PLA was dissolved in 20 mL of CHCl3 to obtain solution II. Solution I and solution II were ultrasonically blended to obtain a membrane-forming solution.
[0119] The obtained film-forming solution was subjected to ultrasonic treatment to remove bubbles, poured into a mold, and dried at room temperature for 72 hours to obtain a C-TETA@CNCs / PLA composite film, wherein the mass fraction of C-TETA@CNCs was 5wt%.
[0120] The cellulose nanocrystals modified with triethylenetetramine, Example 10 and carboxylated cellulose nanocrystals were characterized by Fourier transform infrared spectroscopy (FT-IR). Figure 2 shown.
[0121] According to the film and sheet gas permeability determination method described in GB / T 1038-2000, the test conditions are controlled as follows: temperature 22°C, humidity 35%, oxygen cylinder pressure 0.4MPa, and the oxygen permeability coefficient of the prepared degradable composite film material is measured and recorded as P. At the same time, the pure PLA composite film is prepared under the same conditions, and the oxygen permeability coefficient of the pure PLA film is measured and recorded as P0. The composite film with better barrier properties has a smaller oxygen permeability coefficient, and the test results are listed in the following table.
[0122] Table 1 Oxygen permeability coefficient of composite membrane
[0123]
[0124]
[0125] In order to further illustrate the effect of the oxygen barrier film prepared by the present invention, unmodified cellulose nanocrystal / PLA composite film, carboxylated cellulose nanocrystal / PLA composite film, polyethylene glycol-modified cellulose nanocrystal / PLA composite film, octadecylamine-modified cellulose nanocrystal / PLA composite film and aminated cellulose nanocrystal / PLA composite film were prepared as comparative examples.
[0126] Comparative Example 1
[0127] Referring to the membrane preparation process in Example 26, cellulose nanocrystals (CNCs) were used instead of C-TETA@CNCs to prepare a CNCs / PLA composite membrane, and the mass fraction of CNCs was 3 wt%.
[0128] Comparative Example 2
[0129] Referring to the membrane preparation process in Example 26, carboxylated cellulose nanocrystals (TOCNCs) were used instead of C-TETA@CNCs to prepare a TOCNCs / PLA composite membrane, and the mass fraction of TOCNCs was 3 wt%.
[0130] Comparative Example 3
[0131] (1) 150 mg TOCNCs were placed in 100 ml deionized water and ultrasonicated for 1 h until completely dispersed; 150 mg EDC and NHS were added to activate the carboxyl groups, and the mixture was stirred at 300 rpm for 30 min at room temperature; 0.3 mmol amino-terminated polyethylene glycol was added, and the pH was adjusted to 4.5 with hydrochloric acid; the mixture was stirred at 300 rpm for 24 h at room temperature; after the reaction, the mixture was dialyzed in deionized water until neutral, centrifuged and freeze-dried to obtain polyethylene glycol-modified cellulose nanocrystals (PEG@CNCs).
[0132] (2) Referring to the membrane preparation process in Example 26, PEG@CNCs was used instead of C-TETA@CNCs to prepare a PEG@CNCs / PLA composite membrane, wherein the mass fraction of PEG@CNCs was 3 wt%.
[0133] Comparative Example 4
[0134] (1) Referring to the modification method in Comparative Example 3, 1 g of DMF solution containing 0.3 mmol of octadecylamine (ODA) was used to replace 0.3 mmol of amine-terminated polyethylene glycol to prepare octadecyl-modified cellulose nanocrystals (ODA@CNCs);
[0135] (2) Referring to the film preparation process in Example 26, ODA@CNCs were used instead of C-TETA@CNCs to prepare an ODA@CNCs / PLA composite film, and the mass fraction of ODA@CNCs was 3 wt%.
[0136] Comparative Example 5
[0137] (1) 150 mg of TOCNCs was placed in 100 ml of deionized water and ultrasonicated for 1 h, 150 mg of EDC and NHS were added thereto, and the mixture was stirred at 300 rpm for 30 min at room temperature; 0.3 mmol of triethylenetetramine was added, and the pH was adjusted to 4.5 with hydrochloric acid; the mixture was stirred at 300 rpm for 24 h at room temperature, and the mixture was dialyzed to neutrality in deionized water, centrifuged, washed, and freeze-dried to obtain triethylenetetramine-modified cellulose nanocrystals (TETA@CNCs);
[0138] (2) Referring to the membrane preparation process in Example 26, TETA@CNCs was used instead of C-TETA@CNCs to prepare triethylenetetramine-modified cellulose nanocrystal TETA@CNCs / PLA composite membrane, and the mass fraction of TETA@CNCs was 3 wt%.
[0139] Table 2 Composite membrane oxygen permeability coefficient
[0140]
[0141] It can be seen from the test results that the modification of the amphiphilic molecular chain has greatly improved the oxygen barrier performance. Oxygen permeability is a standard for quantifying oxygen barrier performance. The smaller the oxygen permeability coefficient, the better the oxygen barrier performance. The oxygen permeability coefficient of the C-TETA@CNCs / PLA composite film decreased by 91% compared with the unmodified TOCNCs / PLA, decreased by 86% compared with the octadecylamine-modified ODA@CNCs / PLA composite film, decreased by 81% compared with the polyethylene glycol-modified PEG@CNCs / PLA composite film, and decreased by 83% compared with the triethylenetetramine-modified TETA@CNCs / PLA composite film. The present invention improves the dispersibility and interfacial bonding strength of cellulose nanocrystals in PLA by grafting amphiphilic molecular chains. The amine groups on the polar chains on the surface of the cellulose nanocrystals form hydrogen bonds with the carbonyl groups in the polylactic acid, thereby enhancing the interfacial bonding strength between the cellulose nanocrystals and the polylactic acid. At the same time, the hydrophobic segments on the surface of cellulose nanocrystals can not only enhance the compatibility with hydrophobic polylactic acid, but also act as a "cap" to hinder the interaction between cellulose nanocrystals, significantly reducing the agglomeration of cellulose nanocrystals. Therefore, the grafted amphiphilic molecular chains can ensure good dispersibility while enhancing the interfacial bonding strength. The synergistic effect of the two aspects can maximize the excellent barrier performance enhancement effect of cellulose nanocrystals and achieve high oxygen barrier properties of CNCs / PLA composite films. Therefore, compared with the modifier structure of a single polar carbon chain (such as octadecylamine or polyethylene glycol) in the prior art, cellulose nanocrystals modified with an amphiphilic molecular chain structure have greater advantages in improving the barrier properties of polylactic acid materials.
[0142] The base material PLA and filler CNCs used in the oxygen barrier film of the present invention are both bio-based and degradable, completely avoiding the use of petroleum-based polymers, and can achieve complete degradation, thereby solving the white environmental pollution problem caused by existing petroleum-based polymers from the root and effectively alleviating the dependence on petroleum resources. The oxygen barrier film of the present invention can be used in the field of food packaging, and can be used as a packaging bag or a cling film in the packaging and preservation of vegetables, fruits and melons, and has a wide range of applications.
[0143] The oxygen barrier film provided by the present invention can be used as a fresh-keeping packaging bag for vegetables, fruits and melons. For example: the packaging bag made by the oxygen barrier film provided by the present invention can be used for the fresh-keeping packaging of broccoli. Comparative experiments show that after the broccoli is stored in a fresh-keeping packaging bag made of the oxygen barrier film provided by the present invention, the room temperature shelf life of the broccoli is extended by 23 days compared with unpackaged broccoli; compared with conventional PE cling film, the shelf life can be extended by 16 days. The oxygen barrier film provided by the present invention is made into a cling film, which can be used to preserve fruits such as strawberries and cherry tomatoes. Comparative experiments show that by using the oxygen barrier film provided by the present invention to make a cling film to package fruits such as strawberries and cherry tomatoes, the fresh-keeping period of the fruits can be extended by more than 5 times.
[0144] In addition, the oxygen barrier film provided by the present invention has good degradability and can be degraded in the natural environment after use as a food packaging material, and has environmentally friendly characteristics. The oxygen barrier film provided by the present invention is made into packaging bags and cling film, and can be completely degraded in the natural environment of soil in 5 months; in seawater, it can be completely degraded in about 30-60 days under room temperature conditions, indicating that the oxygen barrier film provided by the present invention is made into packaging bags and cling film. The oxygen barrier film provided by the present invention is made into packaging bags and cling film, and the polymer film is completely broken within 7 weeks under sunlight exposure, and there is no obvious polymer film material within 3 months, and it has good photodegradation ability. In contrast, conventional polyethylene film materials are basically not degraded at all, and the problem of white pollution in the environment is serious.
[0145] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A bio-based degradable oxygen barrier film, characterized in that: It is composed of polylactic acid and amphiphilic molecular chain-grafted modified cellulose nanocrystals, wherein the mass percentage of amphiphilic molecular chain-grafted modified cellulose nanocrystals in the oxygen barrier film is 1-5%, the cellulose nanocrystals are carboxylated cellulose nanocrystals, and the amphiphilic molecular chain is -(NH-CH2-CH2) x -NH-(CH2) y-1 -CH3, wherein x is 2, 3, 4 or 5, and y is 1, 2, 3 or 4.
2. A bio-based degradable oxygen barrier film according to claim 1, characterized in that: The amphiphilic molecular chain grafted modified cellulose nanocrystals are prepared by an amidation reaction between the carboxyl groups on the surface of the carboxylated cellulose nanocrystals and the terminal amine polar molecular chains to form aminated cellulose nanocrystals, and then by a reductive amination reaction between the amine groups on the surface of the aminated cellulose nanocrystals and fatty aldehydes.
3. A bio-based degradable oxygen barrier film according to claim 2, characterized in that: The ratio of the terminal amine polar molecular chain to the carboxylated cellulose nanocrystal is 2-20 mmol:1 g; the terminal amine polar molecular chain is at least one of diethylenetriamine, triethylenetetramine, tetraethylenepentamine and pentaethylenehexamine; The ratio of the fatty aldehyde to the aminated cellulose nanocrystals is 2-20 mmol:1 g; the fatty aldehyde is at least one of formaldehyde, acetaldehyde, propionaldehyde and butyraldehyde.
4. The method for preparing a bio-based degradable oxygen barrier film according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Dispersing carboxylated cellulose nanocrystals in water, adding a carboxyl activator and an amine-terminated polar molecular chain, adjusting the pH, reacting at room temperature for 12 to 48 hours, and obtaining an aqueous dispersion of aminated cellulose nanocrystals by membrane dialysis; (2) Adding fatty aldehyde and reducing agent to the aqueous dispersion of aminated cellulose nanocrystals, reacting at room temperature for 12 to 48 hours, and then centrifuging, washing, and freeze-drying to obtain amphiphilic molecular chain-grafted modified cellulose nanocrystals; (3) The amphiphilic molecular chain grafted modified cellulose nanocrystals are subjected to solvent replacement to obtain an amphiphilic molecular chain grafted modified cellulose nanocrystal dispersion, i.e., solution I; PLA is dissolved in a solvent to obtain solution II; solution I and solution II are evenly mixed to obtain a film-forming liquid, which is defoamed and dried to obtain a bio-based degradable high oxygen barrier film.
5. The method for preparing a bio-based degradable oxygen barrier film according to claim 4, characterized in that: The carboxyl activator in step (1) is N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl); the mass ratio of 1-ethyl-(3-dimethylaminopropyl), N-hydroxysuccinimide and carboxylated cellulose nanocrystals is (0.5-2):(0.5-2):1; In step (1), the ratio of the terminal amine polar molecular chain to the carboxylated cellulose nanocrystal is 2-20 mmol:1 g; the terminal amine polar molecular chain is at least one of diethylenetriamine, triethylenetetramine, tetraethylenepentamine and pentaethylenehexamine; The pH in step (1) is 3-6.
6. The method for preparing a bio-based degradable oxygen barrier film according to claim 4, characterized in that: In step (2), the ratio of the fatty aldehyde to the carboxylated cellulose nanocrystals is 2-20 mmol:1 g; the fatty aldehyde is at least one of formaldehyde, acetaldehyde, propionaldehyde and butyraldehyde; The reducing agent in step (2) is sodium triacetoxyborohydride; the ratio of the reducing agent to the carboxylated cellulose nanocrystals is 2-20 mmol:1 g.
7. The method for preparing a bio-based degradable oxygen barrier film according to claim 4, characterized in that: In step (3), the concentration of solution I is 0.1-5 mg / mL; the concentration of solution II is 0.01-0.5 g / mL; and the volume ratio of solution I to solution II is (1-5):
1.
8. The method for preparing a bio-based degradable oxygen barrier film according to claim 4, characterized in that: The solvent replacement in step (3) refers to: dispersing the amphiphilic molecular chain grafted modified cellulose nanocrystals in dimethylformamide, and replacing them with acetone and / or ethanol, chloroform and / or dichloromethane in sequence to obtain a chloroform dispersion of the amphiphilic molecular chain grafted modified cellulose nanocrystals; wherein acetone and / or ethanol can be replaced with a solvent that is miscible with dimethylformamide and chloroform / and / or dichloromethane and has a dispersibility for CNCs between DMF and chloroform / and / or dichloromethane; the solvent of the solution II is at least one of chloroform and dichloromethane; The concentration of the amphiphilic molecular link grafted modified cellulose nanocrystals dispersed in dimethylformamide is 0.1-3 mg / mL; the concentration in chloroform and / or dichloromethane is 0.1-5 mg / mL; The concentration of the aqueous dispersion of aminated cellulose nanocrystals in steps (1) and (2) is 0.1 to 3 mg / mL; The concentration of the carboxylated cellulose nanocrystals dispersed in water in step (1) is 0.1 to 3.0 mg / ml.
9. The method for preparing a bio-based degradable oxygen barrier film according to claim 4, characterized in that: The drying in step (3) is carried out at room temperature for 48 to 72 hours; the room temperature refers to 10 to 30° C.; the room temperature in steps (1) to (2) refers to 10 to 40° C.
10. Use of the bio-based degradable oxygen barrier film according to any one of claims 1 to 3 in the field of food packaging.
Citation Information
Patent Citations
Method for preparing cellulose nanocrystalline-based room-temperature self-healing environment-friendly composite material
CN108892938A
High-strength polylactic acid-based electrospun nanofiber membrane and preparation method thereof
CN112981704A